HRM in Africa: Exploring the Perceptions of Human Resource Management (HRM) in Ghana - Boakye, Josy-Baroness (2018)
This study examines the perceptions of human resource management (HRM) in Ghana to better understand how context impacts the management of people. The research was explored qualitatively by interviewing people living and working in Accra, Ghana. Cultural, socio-economic and institutional elements were found to impact how HRM was viewed within that environment thus proving that HRM is inherently context-specific. This study also discusses how the defining elements of HRM are centred on Western principles and argues that cultural nuances should be considered when exploring how HRM is delivered in a context outside the West. This works to bridge the gap between the theory and practice of HRM, whilst broadening the discussion of management practices outside a Western perspective and showcasing diversity in HRM.